Strong CPL of achiral liquid crystal fluorescent polymer via the regulation of AIE-active chiral dopant. Issue 84 (23rd September 2020) - Liu, Kerui; Shen, Yihao; Li, Xiaojing; Zhang, Yu; Quan, Yiwu; Cheng, Yixiang
Abstract : Strong CPL induced by ternary polymer dispersed cholesteric liquid crystals (PD-CLCs) can deliver a new strategy for designing excellent CPL materials. Abstract : Ternary polymer dispersed cholesteric liquid crystals (PD-CLCs) prepared by doping AIE-active binaphthyl-based molecules ( R / S -AD, chiral dopant) and the achiral liquid crystal fluorescent polymer, poly( p -phenylene ethynylene) (LC-PPE, CPL emitter) into 5CB, can emit strong circularly polarized luminescence (CPL) with g em up to 0.97. This work develops a new strategy for designing strong CPL materials.